Cost, revenue, and profit efficiency of Islamic versus conventional banks: international evidence using data envelopment analysis - Bader, Mohammed Khaled I.; Ramadilli Mohd, Shamsher Mohamad; Syed Mohamed, Mohamed Ariff; Hassan, Taufiq (Islamic Research and Training Institute, 2008)
This paper measures and compares the cost, revenue and profit efficiency of 43 Islamic and 37 conventional banks over the period 1990-2005 in 21 countries using Data Envelopment Analysis. It assesses the average and overtime efficiency of those banks based on their size, age, and region using static and dynamic panels. The findings suggest that there are no significant differences between the overall efficiency results of conventional versus Islamic banks. Overall, the results in this paper are favorable with the ‘new’ banking system.